2008
DOI: 10.1021/jf800074p
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Damage Mediated by Herbicides on Yeast Cells

Abstract: Agricultural herbicides are among the most commonly used pesticides worldwide, posing serious concerns for both humans, exposed to these chemicals through many routes, and the environment. To clarify the effects of three herbicides as commercial formulations (namely, Pointer, Silglif, and Proper Energy), parameters related to oxidative issues were investigated on an autochthonous wine yeast strain. It was demonstrated that herbicides were able to affect the enzymatic activities of catalase and superoxide dismu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 49 publications
(58 reference statements)
0
18
0
Order By: Relevance
“…Multiple studies have reported the effects of herbicides on yeast biological parameters. Herbicide treatments are able to affect yeast growth by affecting the enzymatic activity of catalase and superoxide dismutase, as well as inducing oxidative modifications of proteins 27 .…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies have reported the effects of herbicides on yeast biological parameters. Herbicide treatments are able to affect yeast growth by affecting the enzymatic activity of catalase and superoxide dismutase, as well as inducing oxidative modifications of proteins 27 .…”
Section: Resultsmentioning
confidence: 99%
“…Defining the decisive molecular balance of living beings as that maintained between reactive species and anti-reactive species, as opposed to the original balance defined as that between oxidants and antioxidants changes how we think of the causes of disease. It unifies the causes of diseases as depicted by Based on the research results up to now, excess species are observed inside living beings, whether from internal factors such as genetic defects [49] and immune reactions [50], or from external factors such as infections [51], toxification [52], mechanical damage including (e.g., burning, radiation, freezing) [53], nutritional deficiency [54], or hypoxia. [55].…”
Section: Resultsmentioning
confidence: 99%
“…They also allowed us to highlight how significant amounts of herbicides can inhibit initial wine-making steps and have negative impacts on yeast fermentative ability, being fermentation the most important biological process that oenological S. cerevisiae strains are supposed to properly carry out. Protein oxidation, and specifically carbonylation [96,97] and thiol oxidation [97,98] of enzymes involved in the fermentative processes as well as in the cell rescue and defense, was suggested to play a key role in herbicide-induced toxicity. Interestingly, we were also able to show a nearly random carbonylation of proteins in response to the herbicide Proper Energy [96], a phenomenon that might mediate the dramatic effects that this specific herbicide was found to have in our yeast model [99].…”
Section: Active Ingredients Vs Pesticide Formulationsmentioning
confidence: 99%